2011
DOI: 10.1094/ats-2011-0425-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year Roughstalk Bluegrass Control in Creeping Bentgrass with Bispyribac-sodium and Sulfosulfuron

Abstract: Bispyribac‐sodium and sulfosulfuron are labeled for roughstalk bluegrass control in creeping bentgrass but comprehensive investigations are limited for long‐term control. The objective of these field experiments was to investigate roughstalk bluegrass control with these herbicides on a creeping bentgrass fairway over three years. Bispyribac‐sodium was applied twice at 37, 74, or 111 g a.i./ha or thrice at 37 or 74 g/ha. Sulfosulfuron was applied twice or thrice at 6.5 or 13 g a.i./ha or once at 26 g/ha. Creepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…This was especially true for fall applications , which injured creeping bentgrass ≥60%, 4 times the injury level caused by the spring applications (data not shown). Bispyribac-sodium efficacy for controlling roughstalk bluegrass in creeping bentgrass has been reported by other researchers, but trends were inconsistent and dependent on creeping bentgrass cultivars, trials, and temperature (McCullough and Hart 2006; McCullough and Hart 2011; Morton et al 2007; Thompson et al 2016).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This was especially true for fall applications , which injured creeping bentgrass ≥60%, 4 times the injury level caused by the spring applications (data not shown). Bispyribac-sodium efficacy for controlling roughstalk bluegrass in creeping bentgrass has been reported by other researchers, but trends were inconsistent and dependent on creeping bentgrass cultivars, trials, and temperature (McCullough and Hart 2006; McCullough and Hart 2011; Morton et al 2007; Thompson et al 2016).…”
Section: Resultsmentioning
confidence: 74%
“…Limited research is available on application timings and rates of methiozolin, alone or tank-mixed with currently available herbicides, for long-term roughstalk bluegrass control in creeping bentgrass turf managed at heights typical of golf fairways or athletic fields. In a multiyear study, McCullough and Hart (2011) found that sequential summer applications of bispyribac-sodium and sulfosulfuron suppressed roughstalk bluegrass cover in a creeping bentgrass fairway. However, cover suppression was apparent only during months of treatment application, and roughstalk bluegrass regrowth in fall following sequential summer applications of bispyribac-sodium and sulfosulfuron resulted in no roughstalk bluegrass cover reduction 10 months after the last treatment of a 2-yr application program.…”
mentioning
confidence: 99%
“…RB has become a frequent weed problem in desirable cool-season turfgrass lawns and seed crops. There are very limited chemical or cultural control methods for this weed species in mixed-stand conditions (McCullough and Hart 2011). Unfortunately, in the Willamette Valley of Oregon, the major production area of cool-season forage and turfgrass seed in the world, this weed species has increased rapidly in the past decade in some waterlogged fields of tall fescue (TF) and other cool-season grass seed crops.…”
mentioning
confidence: 99%
“…
R ough bluegrass (RBG; Poa trivialis L.) is a perennial cool-season turfgrass and a problematic weed in coolseason turf due to suboptimal color, invasive stoloniferous growth, and sensitivity to heat and drought. Naturalized populations spread vegetatively during routine aeration and from contamination in seed lots (Reicher et al, 2011).Bispyribac-sodium (Velocity) is the only product currently labeled for selective RBG removal in cool-season turf and is effective, but it can damage desirable species (McCullough and Hart, 2011) and is only labeled for sod-farm and golfcourse use. Nonselective herbicides are often the only option for RBG control in home lawns, but it is unclear if efficacy varies with seasonal application timing, like RBG response to bispyribac-sodium (McCullough and Hart, 2011).
…”
mentioning
confidence: 99%
“…Bispyribac‐sodium (Velocity) is the only product currently labeled for selective RBG removal in cool‐season turf and is effective, but it can damage desirable species (McCullough and Hart, 2011) and is only labeled for sod‐farm and golf‐course use. Nonselective herbicides are often the only option for RBG control in home lawns, but it is unclear if efficacy varies with seasonal application timing, like RBG response to bispyribac‐sodium (McCullough and Hart, 2011). Rough bluegrass persistence is anecdotally reported after late‐summer glyphosate application.…”
mentioning
confidence: 99%